DETERMINATION of TOTAL FLAVONOID LEVELS on LEAF STALKS ETHANOL EXTRACT of TARO (Colocasia esculenta[L.]Schott) - Novena Yety Lindawati (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2018)
Taro is plant that has a pseudostalk,cylindrical and light brown bulbs. The shape of leaf is the heart in length. Leaf stalk of taro contains are saponins, flavonoids, tanins, alkaloids, steroids and terpenoids. Leaf stalk of taro can be used as an alternative medicines wound and antioxidants. Flavonoids have an important role in the biological activity of taro leaf stalk. This research aims to determine the flavonoid and total flavonoids content in the taro leaf stalk extract. The extraction is done using maceration method with 70% ethanolas solvent. The extract which is got is used for qualitative and quantitative analysis. Quercetin used as a standard solution. Quantitative analysis using UV-Vis Spectrophotometry on a wavelength of 435.5 nm and operating time at the 29th minute. The results of qualitative test showed that the extract was positive flavonoids. The average concentrations of total flavonoids was 10,2223mg QE/gram extract with %CV value of 0,3051%.